Голосовий асистент для україномовних користувачів - Кулик, А. О. (ХНУРЕ, 2023)
In recent years, virtual assistants with artificial intelligence have become increasingly popular, occupying a leading place in our daily lives. With built-in machine learning and natural language processing, these technologies can transform routine actions into more convenient and efficient ones, providing support and simplifying tasks. Voice assistants are integrated into various technological devices, including smartphones, laptops and desktop computers, game consoles, televisions, smart speakers (audio systems) and cars. They can use the voice modality as a centralized way of communication, making the graphical user interface unnecessary or less meaningful.